2017
DOI: 10.1152/ajplung.00453.2016
|View full text |Cite
|
Sign up to set email alerts
|

Reduced carboxylesterase 1 is associated with endothelial injury in methamphetamine-induced pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension is a complication of methamphetamine use (METH-PAH), but the pathogenic mechanisms are unknown. Given that cytochrome P450 2D6 (CYP2D6) and carboxylesterase 1 (CES1) are involved in metabolism of METH and other amphetamine-like compounds, we postulated that loss of function variants could contribute to METH-PAH. Although no difference in CYP2D6 expression was seen by lung immunofluorescence, CES1 expression was significantly reduced in endothelium of METH-PAH microvessels. Mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 66 publications
0
18
0
1
Order By: Relevance
“…Furthermore, chronic amphetamine exposure in hypoxic mice leads to suppression of HIF1a (hypoxia-inducible factor 1-a) and disruption of adaptive responses to mitochondrial oxidative stress, resulting in DNA damage and ultimately vascular injury (31). Finally, as with all drugand toxin-related PAH, a minority of exposed individuals develop PAH, suggesting varying susceptibility from a potential "second hit," such as genetic (32), epigenetic, and environmental factors, or even route, chronicity, or dose of administration (33).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, chronic amphetamine exposure in hypoxic mice leads to suppression of HIF1a (hypoxia-inducible factor 1-a) and disruption of adaptive responses to mitochondrial oxidative stress, resulting in DNA damage and ultimately vascular injury (31). Finally, as with all drugand toxin-related PAH, a minority of exposed individuals develop PAH, suggesting varying susceptibility from a potential "second hit," such as genetic (32), epigenetic, and environmental factors, or even route, chronicity, or dose of administration (33).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that methamphetamine uptake is highest within the lungs, possibly contributing to direct pulmonary toxicity and vascular damage ( 11 ). Other studies have attributed damage to similarities between methamphetamines and serotonin, as serotonin may promote pulmonary smooth muscle cell proliferation and vascular remodeling or even induce DNA damage and impair the oxidative stress response ( 12 , 13 ). Clinically, there have been few studies specifically evaluating patients with Meth-APAH.…”
mentioning
confidence: 99%
“…The membranes were then blocked with 3% BSA, incubated with rabbit polyclonal anti-human CES1 antibody (1:5000) and subsequently incubated with secondary goat anti-rabbit IgG (1:5000) (Abcam, Cambridge, MA). Anti-human CES1 antibody was prepared in a manner previously described [12, 27]. Membranes were imaged on a ChemiDoc MP (Bio-Rad, Hercules, CA) using SuperSignal West Femto ECL Detection Reagent (Thermo Scientific, Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, hCE1 is associated with cholesterol ester metabolism, an activity that prevents the conversion of macrophages into foam cells, which are major players in the development of atherosclerosis [11]. hCE1 has also been implicated in the progression of pulmonary arterial hypertension in methamphetamine users [12]. Finally, hCE1 is suspected to mediate tumoricidal activity in monocytes because patients with non-Hodgekins lymphoma and gastrointestinal carcinoma have altered esterase activity in these cells [13].…”
Section: Introductionmentioning
confidence: 99%